Civilian walking blood bank emergency preparedness plan. Issue Volume 61:Issue S1 (2021)Supplement (16th July 2021) - Holcomb, John B.; Spinella, Philip C.; Apelseth, Torunn Oveland; Butler, Frank K.; Cannon, Jeremy W.; Cap, Andrew P.; Corley, Jason B.; Doughty, Heidi; Fitzpatrick, Michael; Goldkind, Sara F.; Gurney, Jennifer M.; Homer, Mary J.; et al.
Abstract: Background: The current global pandemic has created unprecedented challenges in the blood supply network. Given the recent shortages, there must be a civilian plan for massively bleeding patients when there are no blood products on the shelf. Recognizing that the time to death in bleeding patients is less than 2 h, timely resupply from unaffected locations is not possible. One solution is to transfuse emergency untested whole blood (EUWB), similar to the extensive military experience fine‐tuned over the last 19 years. While this concept is anathema in current civilian transfusion practice, it seems prudent to have a vetted plan in place. Methods and Materials: During the early stages of the 2020 global pandemic, a multidisciplinary and international group of clinicians with broad experience in transfusion medicine communicated routinely. The result is a planning document that provides both background information and a high‐level guide on how to emergently deliver EUWB for patients who would otherwise die of hemorrhage. Results and Conclusions: Similar plans have been utilized in remote locations, both on the battlefield and in civilian practice. The proposed recommendations are designed to provide high‐level guidance for experienced blood bankers, transfusion experts, clinicians, and health authorities. Like with all emergency preparedness, it is always better to have a well‐thought‐out and trained plan in place, rather than trying to develop a hasty plan in the midst of a disaster. We need to prevent the potential for empty shelves and bleeding patients dying for lack of blood.